THE LACK OF FINANCIAL EDUCATION IN BRAZILIAN FAMILIES - Terminelis da Silva, Reliton; Torres Gonzaga Terminelis, Evany (Journal of Interdisciplinary Debates, 2023)
This research Works deals with a topic that has been of great concern since ancient times, the lack of financial education and its impacts on daily life, although here this approach is restricted to Brazilian families, it is also seen with caution in other countries. In this context, most families have little or no knowledge about financial education, thus making it difficult to interpret their budgets, which weighs on the planning of resources for eventual emergencies. Faced with this reality, it is necessary to identify factors that influence the learning process of financial mathematics that were not previously acquired and seek coherent solutions, thus promoting satisfactory results of this knowledge. Therefore, knowing the reality of the consumer is essential to direct a spending limit consistent with his profile, even seeking the use of some financial technological resources related to basic operations as a way to enhance learning. This research is of a bibliographic nature, with the purpose of analysis and reflection with regard to financial education in Brazilian homes and factors that contribute to the difficulties encountered in managing their earnings, as well as the commitment of personal achievements. To this end, materials were collected on financial education websites, financial management books, investment blogs, finance, scientific articles and in all possible collection means that will enrich this study and thus be able to direct more attention to families that encounter these difficulties. Further aggravated by the pandemic.